The Transcriptional Complex Sp1/KMT2A by Up-Regulating Restrictive Element 1 Silencing Transcription Factor Accelerates Methylmercury-Induced Cell Death in Motor Neuron-Like NSC34 Cells Overexpressing SOD1-G93A - Guida, Natascia; Sanguigno, Luca; Mascolo, Luigi; Calabrese, Lucrezia; Serani, Angelo; Molinaro, Pasquale; Lau, C. Geoffrey; Annunziato, Lucio; Formisano, Luigi (Frontiers in Neuroscience, 2021)
.Methylmercury (MeHg) exposure has been related to amyotrophic lateral sclerosis (ALS) pathogenesis and molecular mechanisms of its neurotoxicity has been associated to an overexpression of the Restrictive Element 1 Silencing Transcription factor (REST). Herein, we evaluated the possibility that MeHg could accelerate neuronal death of the motor neuron-like cells NSC34 transiently overexpressing the human Cu2+/Zn2+superoxide dismutase 1 (SOD1) gene mutated at glycine 93 (SOD1-G93A). Indeed, SOD1-G93A cells exposed to 100nM MeHg for 24 hours showed a reduction in cell viability, as compared to cells transfected with empty vector or with unmutated SOD1 construct. Interestingly, cell survival reduction in SOD1-G93A cells was associated with an increase of REST mRNA and protein levels. Furthermore, MeHg increased the expression of the transcriptional factor Sp1 and promoted its binding to REST gene promoter sequence. Notably, Sp1 knockdown reverted MeHg-induced REST increase. Co-immunoprecipitation experiments demonstrated that Sp1 physically interacted with the epigenetic writer Lysine-Methyltransferase-2A (KMT2A). Moreover, knocking-down of KMT2A reduced MeHg-induced REST mRNA and protein increase in SOD1-G93A cells. Finally, we found that MeHg-induced REST up-regulation triggered necropoptotic cell death, monitored by RIPK1 increased protein expression. Interestingly, REST knockdown or treatment with the necroptosis inhibitor Necrostatin-1 (Nec) decelerated MeH-induced cell death in SOD1-G93A cells. Collectively, this study demonstrated that MeHg hastens necroptotic cell death in SOD1-G93A cells via Sp1/KMT2A complex, that by epigenetic mechanisms increases REST gene expression